Aspirin and poetry: did João Cabral de Melo Neto suffer from acetylsali- cylic acid-overuse headache? - Cardoso, Milena Débora; Neto, Pedro Teixeira de Meneses (Headache Medicine, 2023)
Full abstract in PDF.